DIMENSIONES DE LA POLÍTICA (2016)
The present article has as intention identify and analyze the dimensions of the politics. The politics like structure refers to the forms of political organization and to the institutions that integrate the State, that is to say, this dimension is depending on the political regime. The politics like process incorporates the individual conducts and of group that they form the political process, which means that it is in relation with the political system. The politics like result indicates the change and the situations of governance that ensue from the political activity, which in other words is the public policy, for which approaches the concept, the usefulness, the characteristics, the elements, the factors that influence the process of formation of the public policy and the cycle of the public policy integrated by the identification of the problem, the incorporation inside the political agenda, the formulation of solutions and decisions, the implementation and the evaluation.